Limited predictive value of bioelectrical phase angle for the development of sarcopenia in older Europeans - Pigłowska, Małgorzata; Corsonello, Andrea; Kostka, Tomasz; Roller-Wirnsberger, Regina; Wirnsberger, Gerhard; Ärnlöv, Johan; Carlsson, Axel C.; Tap, Lisanne; Mattace-Raso, Francesco; Formiga, Francesc; Moreno-González, Rafael; Kob, Robert; et al. (Journal of Nutrition, Health & Aging, 2024)
Background: Despite the emerging interest in phase angle (PhA), a non-invasive marker of cell hydration and nutritional status, no previous study has reported the prospective association between PhA and incident sarcopenia. Therefore, the aim of our study was to evaluate the association of baseline PhA in older subjects without sarcopenia with the development of new sarcopenia as outcome. Methods: Six-hundred ninety-six subjects without sarcopenia aged ≥75 years enrolled in an international multicenter observational study were included. Sarcopenia was assessed according to the revised EWGSOP2 criteria at baseline and in follow-up visits at 12 and 24 months. Muscle strength was assessed through the handgrip strength test using a hydraulic grip strength dynamometer, muscle mass was assessed by bioimpedance analysis (BIA) and appendicular skeletal muscle mass (ASMM) was estimated. Physical performance was assessed by Short Physical Performance Battery (SPPB). Results: Participants who developed sarcopenia were older, less educated, had higher prevalence of osteoporosis, and lower baseline cognitive function, SPPB, handgrip strength and ASMM than those without sarcopenia. Baseline PhA was significantly lower in subjects developing sarcopenia. Nevertheless, after adjusting for all potential covariates including baseline components of sarcopenia in multiple logistic regression, neither PhA as continuous variable nor different levels of PhA were any more significant predictors of sarcopenia. Conclusions: As an indicator of cells function, PhA could be a potential useful early marker in identifying older people at risk of developing sarcopenia but its practical applicability remains uncertain with the present data.
CRIS-Team Scopus Importer:2024-10-25
Keywords: Aging; Bioimpedance analysis; Elderly; Phase angle; Sarcopenia